Visual respiratory biofeedback to improve visuospatial cognition and cardiac interoception in migraineurs: a study protocol for a randomized controlled trial - Ramaswamy, Krithika A.; Shetty, Shivaprasad; Shetty, Prashanth (Frontiers in Neurology, 2023)
Migraine is a complex neurological disorder which typically presents with unilateral cephalgia associated with cognitive impairment and reduced interoception. These symptoms result in socio-economic repercussions due to reduced productivity, efficiency and work performance. Therefore, along with headache management, improving cognition and interoception should also be significant therapeutic targets to effectively manage migraine.To achieve this, we propose to explore the role of a yoga based visual respiratory biofeedback (VRB) as a possible therapeutic strategy.At least 64 participants will be recruited to trial after screening for eligibility criteria, using the migraine screening questionnaire and Montreal cognitive assessment test. They will be randomly allocated (1:1) to either the experimental group receiving a 20-min session of yoga based VRB or control group who will be asked to watch a documentary film for the same duration. Visuospatial cognition will be assessed by the Corsi block tapping task and cardiac interoceptive accuracy will be assessed by the heartbeat counting task at baseline and immediately after the intervention. Based on the distribution and variance of the data obtained, within group and between group analysis will be conducted using SPSS version 28.0.1.0, with two-sided p<0.05 considered statistically significant.To the best of our knowledge, this is the first study to design and assess the effects of a yogabased biofeedback therapy on cognition and cardiac interoception in migraineurs.Furthermore, we postulated that pranayama's therapeutic effects might be enhanced by using visual yogic respiratory biofeedback. Considering the socio-economic burden of migraine, if found effective VRB investigated in trial could be considered as a therapeutic strategy.This work is registered in ClinicalTrials.gov CTRI Reg No.